The role of customer interactions towards customer satisfaction in theme parks experience - Razak, A.A, Shamsudin, M.F.,; Salem, M.A (Opción, 2019)
The aim of the study is to investigate the role of customer interactions towards customer satisfaction in theme parks experience. Survey was done using self-administrated questionnaire on systematic sampling method. Result shows that interaction contributes towards customer satisfaction but at the same time service providers may also strengthen their service at different factors. In conclusion, interaction also plays an important role to make sure that the tourist feels satisfied besides convenience and willingness to visit theme parks again.